The Influence of Leadership Behaviors Based on the Path-Goal Theory towards Employees’ Satisfaction in a Developing Nation. A Study in the Telecommunication Sector in N’djamena, Chad - Akhaye Idriss Dokony, Hadje; Singh Kartar Singh, Jugindar; Arumugam, Thilageswary (International Journal of Psychosocial Rehabilitation, 2020)
The telecom industry has an important role to play in the performance of a country’s economy. This study is then aimed to investigate and get a clearer view of the relationships that exist between the four leadership behaviors based on the Path Goal Theory, namely supportive, directive, participative, and achievement-oriented, with satisfaction of employees in the telecom companies in Chad. To measure these relationships, quantitative research based on a survey approach was conducted. A sample size of 100 respondents was taken for the research. Convenience sampling was used to collect primary data. Questionnaires were sent by hand to collect cross-sectional data. The data was analyzed using Statistical Program for Social Sciences (SPSS) Version 20. The results revealed that supportive leadership is the preferred leadership style. However, directive leadership had an insignificant relationship with employee’s satisfaction. This study will provide a better understanding to leaders on the appropriate leadership behavior that will improve employee satisfaction. To the best of the researcher’s knowledge, this is the first study of its kind in Chad to examine the influence of leadership behaviors based on the Path-Goal theory towards employees’ satisfaction in the telecommunication sector in n’ Djamena.